Magnetism in disordered carbon as a function of the extent of graphitization - Raj, K. Govind; Joy, Pattayil Alias (Solid State Communications, 2014)
Magnetic properties of disordered carbon have been investigated as a function of the extent of graphitization. It is found that the magnetization of the disordered carbon decreases with increasing degree of graphitization. Treatment with acid modifies the magnetic characteristics considerably and the original magnetic characteristics are retained upon further heat treatment. The results show that the intrinsic magnetic behavior of the disordered carbon depends on the microstructure and that the edge states play a critical role in deciding the magnetic interactions in the amorphous carbon system. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amorphous carbon; disordered carbon; Graphitization; magnetic properties

High surface area nanoporous carbon derived from high quality jute from Bangladesh - Khan, Junayet Hossain; Lin, Jianjian; Young, Christine; Matsagar, Babasaheb M.; Wu, Kevin C. W.; Dhepe, Paresh L.; Islam, Md Tofazzal; Rahman, Md Mahbubur; Shrestha, Lok Kumar; Alshehri, Saad M.; Ahamad, Tansir; Salunkhe, Rahul R.; et al. (Materials Chemistry and Physics, 2018)
We report an economically viable and environment-friendly strategy for the preparation of nanoporous carbon (NC) from jute which is one of the most abundant natural fibers produced in Bangladesh and some South Asian countries. Nitrogen adsorption-desorption isotherms, X-ray diffraction, Raman spectroscopy, UV spectroscopy, and scanning/transmission electron microscopy were performed to characterize the obtained NC. Three different types of jute-derived NCs have been synthesized at three different temperatures, 700 degrees C, 800 degrees C and 900 degrees C. The NC prepared at 800 degrees C resulted in a high surface area (981 m(2) g(-2)) and was associated with the retention of the original fibrous shapes. This study shows a promising future for jute as a natural precursor for NCs for a myriad of applications ranging from water purification to gas separation to energy conversion and storage.
Keywords: Adsorbents; Graphitization; Jute; Nanoporous carbons; porous materials